Effect of intestinal microbiota on growth rate of Babylonia areolata - Wang Zhao; Xingmei Huang; Haipeng Qin; Zhengyi Fu; Rui Yang; Zhenghua Deng; Jinyong Zhu; Danli Wang; Zhongming Zheng (PLoS ONE, 2025)
To analyze the differences in the intestinal microbiota structure of different growth rates of Babylonia areolata, the sequencing of the V3-V4 regions of 16S rDNA from intestinal samples was performed. Evaluation of the richness of microbiota of the samples by calculating Shannon index, Simpson index and Chao1 index showed that the community diversity and richness of the intestinal microbiota of B. areolata changed for different growth rates. There are differences in the diversity of the intestinal microbiota in the fast growth rate (FG) and slow growth rate (SG) groups. A total of 315,294 reads of 16S rDNA were obtained from 6 samples, and 17 phyla were identified by RDP classifier. After data standardization, the dominant phyla from FG and SG were Firmicutes, Proteobacteria, and Bacteroidetes, 50.23%, 39.31% and 8.39% in the FG group, and 79.97%, 12.05% and 6.21% in the SG group, respectively. The distribution of the intestinal microbiota in the FG group is relatively uniform, but the Mycoplasma in the SG group is the dominant genus accounting for about 63%. At the genus level, compared to the SG group, the FG group exhibited a significant increase in the abundance of Exiguobacterium, Vibrio, and Escherichia-Shigella, while the abundance of Mycoplasma, Citrobacter, and Phascolaretobacterum was significantly reduced. These findings provide novel information for studying the differences in the intestinal microbiota of B. areolata with different growth rates, and a foundation for future research on intestinal bacterial factors that may affect the growth and cultivation of B. areolata.